Genetic characterization of some water yam (Dioscorea alata L.) in West Africa with simple sequence repeats - Obidiegwu, J.E.; Asiedu, Robert; Ene-Obong, E.E.; Muoneke, C.O.; Kolesnikova-Allen, M. (2010)
A collection of 89 water yam (Dioscorea alata L.) accessions from Benin, Congo, Côte d’Ivoire, Equatorial Guinea, Gabon, Ghana, Nigeria, Sierra Leone and Togo was assessed for genetic diversity using thirteen microsatellite loci. These 89 are some of the D. alata accessions conserved by the International Institute of Tropical Agriculture (IITA) Ibadan, Nigeria. A total of 97 alleles were detected with an average allele number of 7.46 per locus. Polymorphism information content (PIC) mean value of 0.65 showed existence of variability among the accessions. Accessions from Nigeria showed highest gene diversity of 0.678 while those from Côte d’Ivoire had lowest diversity with 0.596. Observed mean heterozygosity value of 0.469 was observed. Cluster and principal coordinate analysis showed 8 major cluster groups. There was no relationship between relatedness of the accessions and their geographical area of collection. SSR markers proved to be effective to characterise studied D. alata germplasm.